SISTEM INFORMASI ABSENSI SISWA BERBASIS SMS GATEWAY DENGAN MENGGUNAKAN PHP PADA PROGRAM MONITORING ABSENSI PESERTA DIDIK - Anju Parapat; Syaechurodji Syaechurodji (Journal of Innovation And Future Technology (IFTECH), 2020)
Discipline of students and students in the school environment is very important in the process of teaching and learning activities in the school environment, where the discipline can be seen from the results of the attendance attendance of students and students every day. Monitoring student attendance is carried out by each subject teacher who teaches in each class, and then gives it to the student administration staff. The method used in this research is the waterfall method (Waterfall Model) which begins with an analysis of the applications that are running, design, coding, and maintenance of information systems. The author conducts research and looks at student attendance information systems that still have problems that occur. Problems that often occur are the slow process of delivering student absenteeism information to the homeroom teacher, the absence of applications for delivering student absentee information that is fast, accurate and relevant to administrative staff, homeroom teachers, and student guardians, and the absence of student attendance monitoring applications as information media realtime student attendance. Based on the analysis that has been done, it is obtained that, to overcome the problems that occur in the existing student attendance Information System, it is necessary to design and implement a structured system in order to run as expected